An arithmetic logic unit of a computer based on single electron transport system - Biswas, A.K.; Sarkar, S.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
A simple two-way switching can be modified utilizing optical switching, electron-wave modulation and single-electron transport. In this work an arithmetic-logic unit is designed by employing single-electron Binary Decision Diagram devices (or circuits). The design is done for a single bit of the arithmetic-logic unit. The total design will be obtained by cascading desired number of such bit stages.